A new bamboo-feeding species, Mohunia manohari sp. nov., (Hemiptera: Cicadellidae: Deltocephalinae) and first record of the genus from India - Meshram, Naresh M. (Zootaxa, 2021)
A new record for the leafhopper genus Mohunia Distant from India is provided with description of Mohunia manohari sp. nov. (Arunachal Pradesh: Basar). Type material is deposited in the National Pusa Collection, Division of Entomology, Indian Agricultural Research Institute (IARI), New Delhi, India. Illustrations habitus and male genitalia of healthy and parasitized males are given along with an annotated checklist to species of the genus.